In Silico Prediction of The Antiangiogenesis Activity of Heliannuol Lactone sesquiterpenes Compounds from Sunflower (Heliannthus annuus L.) - Muti'ah, Roihatul; Rahmawati, Eka Kartini; Dewi, Tanaya Jati Dhrama; Firdausy, Alif Firman (Indonesian Society for Cancer Chemoprevention, 2021)
Heliannuols are sesquiterpenes lactone compounds considered to have anticancer activity on the brain cancer. Cancer cell growth is related to overexpression of Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2) as a pro-angiogenic pathway, which becomes the main factor of angiogenesis and progression. This research aims to predict anti-angiogenic, toxicity, and physicochemical properties of heliannuols. Physicochemical properties were predicted referred to Lipinski’s rule of five (Lipinski RO5), while absorption, distribution, metabolism, and excretion were predicted by using pkCSM online tool. The toxicity of compounds was predicted by using Protox II online tool, and interaction of the ligand with receptors was predicted by conducting validation (VEGFR-2 (PDB ID: 3WZE)) and molecular docking using Molegro Virtual Docker (MVD). The result revealed that Lipinski RO5 compatible heliannuols had the lowest LD50 2148 mg/kg predictive LD50 predictive values of heliannuol D. The docking result was described by rerank score (RS), representing the bound energy form and compares with Sorafenib as a reference drug. Five medium strength VEGFR-2 chemical substances with rerank score: heliannuol A -56.9496, heliannuol heliannuol B -70.83646, heliannuol C -61,3292, heliannuol D -49.61646, and heliannuol E -75.5164. No better rerank score was recorded for all inhibitors than sorafenib (-128.0683). The heliannuols interacted with amino acid residues Glu885 and Asp1046 that probably conferred the antiangiogenic activity. Taken together, heliannuol D had the greates activity to the target protein and complied Lipinski RO5.Keywords: anti-angiogenic, toxicity, heliannuol, VEGFR-2, brain cancer, molecular docking.